EFFECT OF ADDING CHLOROPHYLL EXTRACT OF SUJI LEAVES (Dracaena angustifolia) AND FERMENTATION TIME ON YOGURT CHARACTERISTICS - Ramadhani, Eko Pramudya; Mustofa, Akhmad; Puyanda, Irvia Resti; Jokopriyambodo, Wahyu (Agric, 2024)
Suji leaves contain a green pigment, namely chlorophyll. Suji leaf chlorophyll and its derivative compounds provide health benefits due to their anti-inflammatory and antioxidant activity. This research aims to produce suji leaf chlorophyll extract yogurt with antioxidant activity, soluble protein levels, and high numbers of lactic acid bacteria. This research used a completely randomized factorial design (CRD) consisting of 2 factors, namely the concentration of added chlorophyll extract (1%, 2%, 3%) and variations in fermentation time (6 hours, 8 hours, 10 hours). The research results showed that suji leaf chlorophyll extract yogurt with antioxidant activity, high levels of soluble protein, and a high number of lactic acid bacteria was found in the treatment with the addition of 3 percent chlorophyll and a fermentation time of 10 hours. In this treatment, suji leaf chlorophyll yogurt was obtained with antioxidant activity of 59.20 percent, dissolved protein content of 128.80 mg BSA/100 ml, total sugar content of 71.92 g glucose/100 ml, fat content of 5.91 percent, total chlorophyll of 2 .39 mg/L, viscosity 10.00 cP; color L* (brightness) 77.09, color a* (reddish) -5.80, color b* (yellowish) 9.35 and total Lactic Acid Bacteria (LAB) around 8.08 Log CFU/mL. Yogurt, with the addition of suji leaf chlorophyll extract, has the potential to be an excellent alternative to functional food for consumption.